Indonesia and Malaysia: Convergence of Syariah Bank Rental and Conventional Bank Credit Agreements - Rahmad Nauli Siregar; Hasim Purba; Utary Maharany Barus; Idha Aprilyana Sembiring (Green Publisher, 2024)
Murabahah products from Islamic banks are often favored by bankers because they mimic conventional bank credit arrangements. The fundamental principle of murabahah is to sell a product at a price equal to the cost of the item plus an agreed-upon profit margin. From this perspective, it is suggested that debt arrangements contain components similar to credit arrangements. This study aims to investigate the relationship between Islamic banking and traditional bank credit agreements using convergence theory, which compares various legal systems or examines how their similarities and differences are correlated. The author uses a qualitative approach by analyzing existing literature on murabahah in Indonesia and Malaysia and applying convergence theory to evaluate the modifications made in murabahah practices in both countries. The study finds that the murabahah applied in Indonesia has several minor modifications that could violate Sharia principles, render the law illegitimate, and negatively affect legal certainty and protection. Malaysia uses the Bai al-Inah contract, which is applied once, whereas Indonesia uses the Murabahah contract, which is applied twice. This difference reflects how Islamic Sharia is implemented and studied in an academic context in both countries. Bai al-Inah is considered a debt, and according to Islamic fiqh, selling debt is prohibited.